Psychosocial characteristics of blood donors influence their voluntary non-medical lapse - Merz, Eva-Maria; Ferguson, Eamonn; van Dongen, Anne (Wiley, 2018)
Background: Approximately 10% of Dutch donors lapse yearly. Common reasons are non-voluntary medical issues (e.g., low Hemoglobin), reaching the upper age limit, and voluntary (e.g., own request, non-response). Little is known about predictors of voluntary non-compliance (lapses). Psychosocial characteristics have been linked to various health behaviors, including voluntary non-compliance. Hence, we investigated whether psychosocial characteristics, measured before the first donation, similarly predict subsequent voluntary non-medical lapse. Study Design and Methods: New donors (N=4,861) randomly received a blood donation survey between July 2008–March 2009, before their first appointment at the blood bank. Voluntary lapses included personal reasons, non-response to invitations, donor cannot be reached, and no-show. Univariate and multivariate Cox regression models of lapse on psychosocial characteristics, and confounders (e.g., demographics) were estimated. Results: Of 2,964 donors who took the questionnaire, over one third (36.5%) had voluntarily lapsed due to non-medical reasons by 2016. Univariate regression showed that lapse negatively associated with norms, attitudes and intentions towards blood donation, self-efficacy and more donation experience. Lapse positively associated with anxiety. Multivariate Cox models showed that lapse was primarily driven by anxiety and need for information. Conclusion: Certain psychosocial characteristics increase risks of voluntary lapse. Especially donors with higher donation anxiety had increased lapsing risks. They might benefit from extra attention during donation. Donors with more information need/wish about procedure and patients were less likely to lapse, indicating that binding with the blood bank might prevent lapse. Generally, this study showed that donor lapse and donor return are determined by different psychosocial factors not just the reverse of each other.